KEBIJAKAN FISKAL DALAM EKONOMI MAKRO ISLAM - Muhammad Arifin Lubis; Asmaul Husna (JURNAL ILMIAH EDUNOMIKA, 2024)
Fiscal policy is a policy that regulates or manages the state's revenue and expenditure with the aim of maintaining stability and promoting economic development. Government revenue and expenditure are among the instruments of fiscal policy. However, in modern literature, fiscal policy does not address ethical issues, except in distribution theory. Even then, it is only limited to distribution theory. This research method uses a library study. The results of this discussion show that fiscal policy in Islam, from the time of the Prophet Muhammad (peace be upon him) until now, has always used a balanced budget system managed through the Baitul Mal. Instruments developed in Islamic fiscal policy include zakat, infaq, sadaqah, waqf, ghanimah, fa’i, kharaj, jizyah, ushur, and khumus.